Writing apprehension in English among Jordanian postgraduate student at Universiti Utara Malaysia (UUM) - Huwari, Ibrahim Fathi; Abd Aziz, Noor Hashima (SAVAP International, 2011)
This research investigated writing apprehension among Jordanian postgraduate students studying at University Utara Malaysia (UUM).Jordanian students lack the ability to write in English at schools or universities level in Jordan because they do very little writing in English.This study had three main objectives: (1) to investigate the levels of Writing Apprehension among the Jordanian postgraduate students when writing in English at UUM (2) to investigate the relationship between age and socio-economic status with writing apprehension (3) to discover the writing situation that make the Jordanian postgraduate students feel most apprehensive when writing in English (writing a thesis, writing assignments, or writing journals).This study used a survey research design. The sampling of this study consisted of one hundred and three Jordanian postgraduate students at UUM.The instrument used in this study was Writing Apprehension Test (WAT) developed by Daly and Miller (1975) to measure writing apprehension. The results of this study showed that majority of the Jordanian postgraduate students experienced high level of writing apprehension.There was a significant relationship between age, socio-economic status and writing apprehension. For the open ended question, majority of the respondents said that they experienced apprehension in writing a thesis more than writing assignments, or writing journals.